PERLINDUNGAN HUKUM BAGI KORBAN SERANGAN RANSOMWARE - Desyanti Suka Asih K.Tus (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Data is an important part of the need in today's Information Technology era. The data of every human individual in the world has a high level of sensitivity for anyone. Data that is currently developing both offline and online data, requires a certain level of security in its access. Good data security techniques are needed in ensuring the confidentiality of a data including from attacks of several types of malware viruses and ransomware.Types of malware viruses and ransomware work with the concept of damaging, stealing and locking data with various purposes, one of which is to make a profit. Ransomware works by locking certain files that are targeted and encrypted so that the data is inaccessible. In the end, if you want to access the stored data, users are required to contact the contact of the creator of the ransoware by paying a certain amount of money in decrypting the locked data. Ransomware can be categorized as cyber extortion. Article 27 paragraph 4 of the ITE Law provides arrangements on the dissemination of information that has extortion content whose provisions are regulated in the Criminal Code. Ransomware meets the elements of the criminal act of extortion as stipulated in the provisions of Article 368 paragraph (1) of the Criminal Code. The perpetrator commits extortion coupled with acidification by closing the victim's access to his data. The government has made legal protection efforts for victims of ransomware among others through the arrangements contained in Article 27 Paragraph (4) of the ITE Law. As well as the application of criminal sanctions of confinement and fines for perpetrators of ransomware crimes. Protection of cyber space users can also be done by individuals (individuals) by building regulations in cyberspace and being vigilant in using the internet. In an effort to provide legal protection for ransomware victims, cooperation is needed between the government as a lawmaker and users (victims of ransomware) cyber space. More advanced and unconventional regulations are critical in dealing with cybercrime. Because all forms of cybercrime cannot be touched by the rule of law.